Education Economics from a Historical Perspective - Ruth Maria Schüler (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2018)
The organization of the Prussian school system still affects the German education system of today. Against the background of end-of-nineteenth-Prussia this thesis analyzes how education funding emerges in a federal system and how it affects prosperity and nation building in a setting of religious and ethno-linguistic heterogeneity. The econometric anal-yses are based on census data, originally collected by the Royal Statistical Office of Prussia and partly digitized for this thesis. The thesis consists of four distinct empirical analyses on educational economics from a historical perspective, two chapters investigating the consequences of educational inputs and two chapters examining the determinants of educational provision and performance in nineteenth-century Prussia. @Die Ausgestaltung des preußischen Schulsystems wirkt sich bis heute auf das deutsche Bildungswesen aus. Auf dem Hintergrund Preußens zu Ende des 19. Jahrhunderts untersucht diese Arbeit, wie sich die Finanzierung eines Bildungssystems in einem föderalen System entwickelt hat und wie eine zunehmende Zentralisierung der Bildungsausgaben sich auf Wohlstand und das Entstehen einer Nation auf dem Hintergrund von religiöser und ethnischer Heterogenität auswirkt. Die ökonometrischen Analysen basieren auf Zensusdaten, die vom Königlich Statistischen Bureaus Preußens erhoben wurden und zum Teil für diese Dissertation digitalisiert wurden. Die Arbeit besteht aus vier eigenständigen empirischen Analysen zur Bildungsökonomik aus historischer Perspektive. Zwei Kapitel untersuchen die Auswirkungen von Bildungsinputs, während die zwei weiteren Kapitel sich mit Bestimmungsgrößen von Bildungsbereitstellung und Bildungsleistung im Preußen des 19. Jahrhundert auseinandersetzen.
Keywords: I21; I22; H41; H52; H75; N13; N33; 330; Education; Public Spending; Prussian Economic History; Human Capital; Economic Development; Industrial Revolution; Nation Building; Indoctrination; Minorities; Polarization; Public Goods; Decentralization; Centralization; Resistance; Monitoring; Accountability